The key is not to forget to be awesome: Identifying narratives in an online community - Escobar, M.; Kommers, Piet; Beldad, A. (Inderscience Publishers, 2014)
As online communities emerge in different settings all over the web, they continue to develop different ways to communicate online and to encourage participation in their activities. Scholars have proposed that one of the ways in which these communities do so is through the use of narratives. A case study was done on an open online community to establish if online communities develop narratives, what kind of narratives, and if these influence participation. This paper contains the analysis of the identifiable narratives that are useful to promote culture and participation and proposes three types of narratives that are more effective to do so. Implications of such findings and proposed future research are discussed.